Exploring the agriculture-nutrition linkage in northern Ghana - Signorelli, Sara; Haile, Beliyou; Kotu, Bekele (International Food Policy Research Institute, 2017)
This study contributes to the literature by examining the agriculture‒nutrition linkage using data from northern Ghana. Specifically, we assess the relative importance of productivity and production diversity in improving household dietary diversity, while at the same time assessing the role of market access. We find that both on-farm production diversity and productivity positively affect household dietary diversity. In addition, the effect of production diversity gets stronger the longer the travel time to the nearest daily market.